2019
DOI: 10.1177/0266666919840698
|View full text |Cite
|
Sign up to set email alerts
|

Managing health records in the Bulawayo and Matabeleland South provinces hospitals, Zimbabwe

Abstract: The purpose of this study was to investigate the management of health records in the Bulawayo and Matabeleland South provinces in Zimbabwe. The objectives of the study were to understand how health records were being managed in the two hospitals, to establish the availability of, and analyse standard procedures and guidelines that informed both the National Archives of Zimbabwe (NAZ) and hospitals in managing health records. The study also sought to establish the level of professional training for health recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…In the long run, poor records management practices could be costly for any institution. The policy status of records management in Sub-Saharan Africa is mostly consistent with the findings of the current study; the overall state of records management policies in Africa as a whole is still undesirable (Osebe et al , 2018; Masuku and Ngulube, 2020).…”
Section: Factors Militating Against Records Management Practicessupporting
confidence: 87%
See 1 more Smart Citation
“…In the long run, poor records management practices could be costly for any institution. The policy status of records management in Sub-Saharan Africa is mostly consistent with the findings of the current study; the overall state of records management policies in Africa as a whole is still undesirable (Osebe et al , 2018; Masuku and Ngulube, 2020).…”
Section: Factors Militating Against Records Management Practicessupporting
confidence: 87%
“…Eventually, this may lead to lapses and dilemmas in executing key decisions such as retention and disposal of records. These findings echo those of other African studies undertaken by Osebe et al (2018) in Kenya, Asogwa et al (2021) in Nigeria, Mosweu (2019) in Botswana and Masuku and Ngulube (2020) in Zimbabwe, which stress that records professionals need to be reskilled to cope within the electronic records landscape.…”
Section: Inadequate Qualified Staff and Trainingsupporting
confidence: 84%
“…Based on the data, the researcher also concluded that the RAM profession was not engaged in image building. This study therefore concluded that the absence of a professional RAM association in Zimbabwe as noted by Masuku (2013), was working against professional image building.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…The findings of this study showed that the Records, Archives and Information Management Association of Zimbabwe (RAIMAZ) was defunct and thus there was no professional association for archivists and records managers in the country. The absence of a professional RAM association was also highlighted by scholars such as Khumalo (2016); Chaterera (2013) and Masuku (2013). Masuku (2013) however, highlighted that efforts are underway to resuscitate RAIMAZ, although at a very slow pace.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation